PENERAPAN MODEL PEMBELAJARAN PJBL (PROJECT BASED LEARNING) UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS SISWA KELAS X.2 SMAN 4 MATARAM TAHUN AJARAN 2022/2023 - Endang Wahyu Marlangen; Syamsul Bahri; Siti Raodah (JURNAL ASIMILASI PENDIDIKAN, 2023)
This research was conducted with the aim of improving the critical thinking skills of class X.2 students at SMAN 4 Mataram after following the learning process using the PjBL learning model. The research method used in this research is Classroom Action Research which was carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation and reflection. The subjects of this research were class X.2 students with a total of 34 students, consisting of 17 male students and 17 female students. The research instrument used is a written test in the form of essay questions which can measure students' critical thinking skills through administering pretests and posttests. The average value of the pretest results for classical students is 45% which is classified as low. There was an increase in cycle I of 62% which was classified as medium category, then increased again in cycle II of 75% which was classified as high category. This shows that students' critical thinking skills have increased from cycle I to cycle II. Therefore, cycle II has met the indicators for achieving student learning outcomes, so it can be concluded that the application of the PjBL learning model can improve the critical thinking skills of class X.2 students at SMAN 4 Mataram.